Pengaruh Kompensasi Non Finansial Terhadap Motivasi Kerja Karyawan di PT. PLN (Persero) Area Bandung - Rucita Pinasti Lugina; Yahya Arwiyah (Lembaga Penelitian Universitas Langlangbuana, 2019)
Non-financial compensation is an attractive and potential reward for motivating employee performance (Walker in Marwansyah, 2014). This research was done at PT PLN (Persero) Bandung Area. The purpose of this study is to determine the effect of non-financial compensation that is provided by PT PLN (Persero) Bandung Area to employee motivation. This research used quantitative research method with causal descriptive type. The data of this research is obtained by distributing questionnaires to 67 employees not including the leader in PT PLN (Persero) Bandung Area. The sampling technique used in this research is saturated sampling (census), the data is processed by descriptive analysis and simple linear regression analysis by Microsoft Excel 2013 and IBM SPSS 21 program.Based on the results of this research shows that the non-financial compensation variable (X) significantly influence by the variable of work motivation (Y) in PT PLN (Persero) Bandung Area. This is evidenced by the significance value 0,000 < 0,05 and tcount (4,313) > ttable (1,669), and on the calculation of determination coefficient obtained that the influence of non-financial compensation to employee work motivation in PY PLN (Persero) Bandung Area is 0,222 or 22,2% and the rest of which is 77,8% influenced by variables or other factors outside of the research variables